Stability of microprocessor relay protection and automation systems against intentional destructive electromagnetic impacts. Part 1 - Gurevich, V.L. (Електротехніка і електромеханіка, 2011)
Problems of impact of electromagnetic high-power pulses generated at nuclear explosion or by means of special equipment intended specially for damage of electronic equipment, in particular, digital protective relays and automatic systems, along with ways of protection against these impacts are considered.